The Sense of Humor Scale: Psychometric Studies on Banjar Ethnic Students - Naufal Syarif Farras; Unggul Haryanto Nur Utomo (Empathy : Jurnal Fakultas Psikologi, 2023)
Skala Kepekaan Humor (SKH): Studi Psikometrik pada Mahasiswa Etnik BanjarThe focus of this study contributes to adding reference to the psychometric property of the Sense of Humor Scale (SKH) which aims to be a culturally fair test. The type of validity used is content validity (logical type) and estimated reliability using the internal consistency method. A total of 50 Banjar ethnic students were the research subjects obtained by the convenience purposive sampling method. The reliability coefficient (alpha) for the violence component was 0.916, the annoyance component was 0.872, the parody component was 0.888 and the creativity component was 0.845. Selection of the initial 76 items of SKH resulted in 64 items that had been adjusted to the proportions of the components in the blue print, the lowest item discrimination power index (rit) was 0.281, the highest was 0.747 and the mean was 0.521. The reliability coefficient of the SKH composite score (Mosier formula) is 0.944, meaning that 94.4% is a pure score for the subject group (5.6% of the difference in the apparent score is due to variations in measurement errors). It was concluded that the results of a psychometric study of SKH in ethnic Banjar students showed empirical evidence that SKH is a valid and reliable measure of humor.